Strategy for the Development of Tangkahan Tourism Objects in Gunung Leuser National Park as a Tourist Destination for Langkat Regency - Yesy Beby Emelya Siregar; R. Hamdani Harahap; Heri Kusmanto (Universitas Medan Area, 2023)
This study aims to determine and explain the strategy for developing the Tangkahan tourist attraction in Gunung Leuser National Park as a tourist destination in Langkat Regency using SWOT analysis. The type of research used is qualitative-descriptive, while data collection techniques use three methods, namely observation, interviews, and documentation. The data analysis technique used is to reduce data, present data, and draw conclusions. Data validation techniques in this study used two types of triangulation, namely technical triangulation and source triangulation. The research results obtained SO strategies: (1) Promote natural potential and various flora and fauna in Langkat Regency by using the development of information technology and social media; (2) Improving the quality of Gunung Leuser National Park as a natural school. WO strategies: (1) improve facilities and infrastructure in the Tangkahan area; (2) Improving the quality of human resources; (3) Educating the public in terms of preserving historical heritage and regional cultural customs. ST strategy: (1) Utilizing and developing natural potential which is still large and beautiful in Tangkahan; (2) Providing Tourism Awareness education and training (DARWIS) and SAR training. WT strategy: (1) Conduct mediation and negotiation (cooperation and partnership) between tourism stakeholders and PTPN; (2) Compile a mapping of historical and archaeological preservation in Langkat Regency.